Polyamide 6/silica hybrid materials by a coupled polymerization reaction1. Issue 35 (21st September 2015) - Kaßner, L.; Nagel, K.; Grützner, R.-E.; Korb, M.; Rüffer, T.; Lang, H.; Spange, S.
<x xml:space="preserve">Abstract</x> Polyamide 6/SiO2 hybrid materials with an adjustable SiO2 amount were produced by the coupled polymerisation of three monomeric components namely 1, 1′, 1′′, 1′′′-silanetetrayltetrakis-(azepan-2-one), 6-aminocaproic acid and ε-caprolactam within one process.